Răspuns :
2 : (2/3)^2 + 11/5 : 11/10 =
= 2 : 4/9 + 11/5 x 10/11 =
= 2 x 9/4 + 10/5 =
= 9/2 + 2 =
= 9/2 + 4/2 =
= 13/2
= 2 : 4/9 + 11/5 x 10/11 =
= 2 x 9/4 + 10/5 =
= 9/2 + 2 =
= 9/2 + 4/2 =
= 13/2
2 : ( 2/3 )² + 11/5 : 11/10 =
= 2 : (2/3)² + 11/5 × 10/11 =
Pentru a ridica o fractie la o putere ridici atat numaratorul cat si numitorul la aceeasi putere
= 2 : 4/9 + 11/5 × 10/11 =
= 2 : 4/9 + 1/5 × 10 =
= 2 : 4/9 + 2 =
= 2 × 9/4 +2 =
= 9/2 + 2 = (9+4)/2 = 13/2
= 2 : (2/3)² + 11/5 × 10/11 =
Pentru a ridica o fractie la o putere ridici atat numaratorul cat si numitorul la aceeasi putere
= 2 : 4/9 + 11/5 × 10/11 =
= 2 : 4/9 + 1/5 × 10 =
= 2 : 4/9 + 2 =
= 2 × 9/4 +2 =
= 9/2 + 2 = (9+4)/2 = 13/2